(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Thalassemia is an inherited disorder. All the types of thalassemia that require continuous blood transfusion, lead to increase of absorption of iron, which will lead to iron overload eventually. The precipitation of iron will affect many organs in the human body, and can be measured by S- ferritin. In this study, patients with all kinds of thalassemia that require multiple blood transfusion, have been evaluated for the level of ferritin and iron overload as well as other complications such as liver diseases, heart diseases, bone disorders, and hormone disorders. One-hundred patients have been selected randomly with different ages to evaluate the serum ferritin, calcium level, liver enzymes, and Hb by use enzyme linked assay. This study confirms the use of chelation therapy to remove the iron overload.